The Importance of Basic Financial Instruments Used in Islamic Banking - Aliqoriev O.F (Zien Journals, 2023)
The article focuses mainly on the importance of basic financial instruments used in Islamic banking, the classification of Islamic financial instruments, and the definition of the instruments of mudoraba, murobaha, mushoraka.
Keywords: Islamic banks; islamic financial instruments; transactional contracts; intermediary contracts